2021
DOI: 10.1002/adhm.202100814
|View full text |Cite
|
Sign up to set email alerts
|

Localized Chemotherapy Based on Injectable Hydrogel Boosts the Antitumor Activity of Adoptively Transferred T Lymphocytes In Vivo

Abstract: The adoptive transfer of antigen-specific T cells has been successfully applied in the treatment of hematological malignancies. However, its application in the treatment of solid tumors has been overshadowed by the immunosuppressive tumor microenvironment. In this context, a preprocessing strategy is developed to reprogram the immunosuppressive tumor microenvironment using a thermoresponsive hydrogel loaded with doxorubicin (DOX@Gel). Compared with hydrogel-based chemotherapy alone or adoptive T cell therapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 58 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…On the other hand, if injected into solution, the composite hydrogels appeared as visible strips, which showed greatly enhanced injectability compared with the hydrogels composited before (Figure S7 in the supporting information). The injectability test demonstrated the superior injectability and self-healing capacity resulting from the great advantages of the composition of both N-FF and HA, which could provide a potential scaffold for in situ tissue regeneration and expand their applications for localized drug delivery in vivo . …”
Section: Results and Discussionmentioning
confidence: 99%
“…On the other hand, if injected into solution, the composite hydrogels appeared as visible strips, which showed greatly enhanced injectability compared with the hydrogels composited before (Figure S7 in the supporting information). The injectability test demonstrated the superior injectability and self-healing capacity resulting from the great advantages of the composition of both N-FF and HA, which could provide a potential scaffold for in situ tissue regeneration and expand their applications for localized drug delivery in vivo . …”
Section: Results and Discussionmentioning
confidence: 99%
“…Especially, thermosensitive biodegradable hydrogels that show rapid thermo‐responsive sol–gel phase transitions around physiological temperature have attracted considerable interest, due to the facile control of the gelation process and bioabsorbability 51–55 . In our previous studies, thermosensitive poly(ethylene glycol)‐polypeptide block copolymer hydrogels have been developed as local depots for sustained delivery of various anti‐tumor agents including chemotherapeutics and immunotherapeutic agents, attributed to the good biocompatibility and unique secondary conformation of polypeptide segments that promotes gel formation 56–61 . It was demonstrated that the localized and prolonged release of anti‐tumor agents by the hydrogels led to increased anti‐tumor efficacy compared to free drug solutions.…”
Section: Introductionmentioning
confidence: 99%
“…[51][52][53][54][55] In our previous studies, thermosensitive poly(ethylene glycol)-polypeptide block copolymer hydrogels have been developed as local depots for sustained delivery of various anti-tumor agents including chemotherapeutics and immunotherapeutic agents, attributed to the good biocompatibility and unique secondary conformation of polypeptide segments that promotes gel formation. [56][57][58][59][60][61] It was demonstrated that the localized and prolonged release of anti-tumor agents by the hydrogels led to increased anti-tumor efficacy compared to free drug solutions. However, the studies on hydrogel-based anti-tumor chemo-immunotherapy systems that are capable of simultaneous ICB blockade and modulation of immunosuppressive TME using IDO inhibitors are still limited.…”
mentioning
confidence: 99%
“…Local administration provides an effective alternative that allows for highly‐targeted and sustained delivery of therapeutic agents while circumventing many issues associated with systemic administration 27–30 . Thereinto, injectable and temperature‐induced gelling systems composed of PEG/polyester copolymers, 31–36 PEG/polypeptide copolymers, 37–41 and poly(phosphazenes) 42,43 have attracted much attention as promising candidates for drug delivery in virtue of their minimal invasive administration and excellent match to complex settings at the target site. Generally, these systems exhibit temperature‐responsive transition from sol state at low or ambient temperature to gel state at physiological temperature 44–48 .…”
Section: Introductionmentioning
confidence: 99%